Centro de desenvolvimento para crianças tea e seus cuidadores - Silva, Gabriela Saraiva Pinheiro e (Brasil, 2022)
The proposal is a Development Center for ASD Children and their caregivers, according to the WHO, 1 in 160 children in the world are affected. The condition called Autism Spectrum Disorder usually has its first manifestations in childhood and persists during adolescence and adulthood, as there is no cure. However, evidence-based psychosocial interventions such as behavioral treatment and parenting skills training programs can reduce communication and social behavior difficulties, with a positive impact on the well being and quality of life of people with ASD. and their caregivers. These interventions need to be accompanied by broader actions, including modification and reflection on built environments, to make them more accessible and inclusive, as a way to address the particular issues of ASD individuals who have greater sensory sensitivities. . The challenges experienced by the built spaces that are frequented daily affect both the child on the spectrum and their caregivers. The responsibility for monitoring and caring for this individual usually completely transforms the caregiver's life dynamics, and what is observed in most cases is a need to abdicate other aspects of life (professional, personal care, time for other activities) so that you can fully assist. Caring for children in the most serious conditions can be demanding, especially where access to services and support is inadequate. Therefore, caregiver empowerment is increasingly recognized as a key component of care interventions for children in these conditions. Considering the high number of children, the need for interventions in childhood for better development, the demand for adequate spaces for the specific treatment of this public that takes into account their spatial and sensory needs, the importance of behavioral, therapeutic and educational treatment is evident. , in an environment that reflects in its form and architecture, the possible solutions for the space to be an element that contributes to this treatment process, optimizing the therapeutic actions developed.